Modeling experimental glaucoma for screening studies of antiglaucomatous activity - Vladimir N. Fedorov; Mikhail K. Korsakov; Vladimir P. Vdovichenko; Salavat S. Suleimanov; Alena N. Tyushina; Anastasiya A. Popova (Belgorod National Research University, 2023)
Introduction: In vivo screening studies, in which the efficacy of dozens of drugs is tested to select several applicants for further study of their safety in humans, are the main stage in the study of the pharmacodynamics of promising antiglaucoma drugs. This imposes a number of specific requirements both on experimental models of glaucoma and on laboratory animals used in the experiment. Materials and Methods: 32 male rabbits of the Soviet Сhinchilla breed, 6 male albino rabbits weighing 3-3.5 kg, and 20 outbred white rats weighing 220-250 g were used in total in experiments to reproduce the glaucoma process. All manipulations on the rabbit eye were performed by an ophthalmologist under general anesthesia with telazol. Triamcinolone (vitreous injection) was used to simulate glaucoma in rabbits, lauromacrogol 400 or fine kaolin (anterior chamber injection) was used to simulate glaucoma in rabbits; adrenaline hydrochloride (intraperitoneal administration) was used to simulate glaucoma in rats. Results and Discussion: Double intravitreal administration of a suspension of triamcinolone at a dose of 4 mg was the most attractive model in terms of the technique of reproducing the pathology and the results obtained in modeling glaucoma in rabbits. However, this model did not produce a stable increase in intraocular pressure (IOP). Doubling the dose of triamcinolone and replacing chinchilla rabbits with albinos did not lead to a positive result. The introduction of the venous sclerosing drug lauromacrogol 400 into the anterior chamber of the eye proved to be ineffective either. The introduction of finely dispersed kaolin into the anterior chamber of the eye of rabbits led to a persistent increase in IOP. The intraperitoneal administration of epinephrine hydrochloride to rats according to the described method gave no stable results. The increase in IOP became stable only after a significant increase in the dose of adrenaline. Conclusion: The conducted studies of four models of glaucoma and their three modifications in animals made it possible to select two of them, which contributed to a stable and fairly long-term increase in IOP in rabbits (introduction of finely dispersed kaolin into the anterior chamber of the eye) and rats (adrenaline-induced model).